GIS-material for the archaeological project: Stone Age remains preceding recycling centre in Krokek - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
The Swedish National Heritage Board's contract archaeology division, UV Öst, has surveyed three areas (object 1-3) within the properties Lösings häradsallmänning, Kolmården 1:6 and Strömsfors 1:1 in Krokek parish, Norrköping municipality. The municipality is planning to build a recycling centre in the Krokek area. Due to this, UV Öst performed a stage 1 survey within objects 1 - 2 and a stage 2 survey within object 3. Archaeological remains consisting of Stone Age settlements were discovered just north-east of object 1 and within part of object 2. No remains were found within object 3.

Purpose:

The information in the purpose is translated from the archaeological report:
The aim of the surveys was to investigate whether the development area contained any archaeological remains protected by law, or any other cultural remnants, and, if so, if the remains were going to be affected by the development works.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har under september 2005 och maj 2006 genomfört arkeologiska utredningar inom tre områden (objekt 1-3) inom fastigheterna Lösings häradsallmänning, Kolmården 1:6 samt Strömsfors 1:1 i Krokeks socken, Norrköpings kommun. Norrköpings kommun avser att etablera en återvinningscentral i Krokeksområdet. UV Öst genomförde med anledning av detta utredning, etapp 1 inom objekt 1-2 samt utredning, etapp 2 inom objekt 3. Den arkeologiska utredningen konstaterade fornlämningar i form av stenåldersboplatser strax nordöst om objekt 1 samt inom del av objekt 2. Inga fornlämningar påträffades inom objekt 3.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med de arkeologiska utredningarna har varit att fastställa om lagskyddade fornlämningar eller andra kulturlämningar var belägna inom undersökningsområdena, och i så fall om dessa skulle komma att beröras av arbetsföretaget.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Stenålder inför återvinningscentral i Krokek
Keywords: stone age; stenålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi